2005
DOI: 10.1074/jbc.m506648200
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Death Receptor-mediated Apoptosis by 1,25-Dihydroxyvitamin D3 Revealed by Microarray Analysis

Abstract: Vitamin D 3 (VD)2 is a steroid hormone best known for its role in calcium homeostasis. Its deficiency causes rickets in children and osteomalacia in adults. VD also regulates the proliferation and differentiation of normal and malignant cells of many tissue types. Because sunlight controls the first step of VD synthesis, namely, the photoconversion of 7-dehydrocholesterol to vitamin D 3 (1), the hormone is considered a "sun" medicine that is effective for the treatment and/or prevention of type II rickets, ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 49 publications
3
58
0
1
Order By: Relevance
“…Although caspase cleavage and the action of other apoptosis-related molecules usually occurs within 24 hours or less, it has been shown that vitamin D acts much more slowly to effect apoptosis. For example, Zhang and colleagues (53,54) have shown the strongest apoptotic response at 6 days following treatment using a vitamin D analog in several cell lines. Mathiasen and colleagues (55) also showed peak vitamin D-induced apoptosis at 6 to 7 days posttreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although caspase cleavage and the action of other apoptosis-related molecules usually occurs within 24 hours or less, it has been shown that vitamin D acts much more slowly to effect apoptosis. For example, Zhang and colleagues (53,54) have shown the strongest apoptotic response at 6 days following treatment using a vitamin D analog in several cell lines. Mathiasen and colleagues (55) also showed peak vitamin D-induced apoptosis at 6 to 7 days posttreatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature vitamin D is often reported to inhibit both proliferation and apoptosis in cancer cells [9,10]. However the detailed signaling pathway for such dual effects has been poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may results in an inhibition of IFN-g induced activation and potentiation of lysosomal activity of macrophages, recruitment of autophagic proteins, and, ultimately, may lead to a decrease of autophagy Wu and Sun (2011) NF-kB expression (?) Bao et al (2010), Krishnan and Feldman (2010), Tse et al (2010), andJanjetovic et al (2011) Induced expression of thioredoxin reductase 1 (TXNRD1) Swami et al (2003), Peehl et al (2004), Kovalenko et al (2010) Antioxidant defense and DNA repair Increased production of superoxide dismutase 1 and 2 (SOD1 and SOD2) in prostate epithelial cells (PECs) and in androgen-sensitive prostate cancer cells (LNCaP) Peehl et al (2004) and Lambert et al (2006) Increase of glucose-6-phosphate dehydrogenase (G6PDH) expression levels Zhang et al (2005), Bao et al (2008), and Kovalenko et al (2010) Induction of nuclear factor erythroid-derived 2-like 2 (NFE2L2) transcription factor that controls the gene expression of several enzymes of the antioxidants systems such as glutathione peroxidase (GPX) 3, heme oxygenase 1 (HMOX-1), and aldo-keto reductase 1C2(AKR1C2)…”
Section: Ink4dmentioning
confidence: 99%
“…In addition, 1,25(OH) 2 D 3 has been shown to increase the production of superoxide dismutase 1 (SOD1) and 2 (SOD2) in prostate epithelial cells (PECs) and in androgen-sensitive prostate cancer cells (LNCaP), respectively (Lambert et al, 2006;Peehl et al, 2004). Furthermore, other in vitro observations show that the treatment of the human prostate epithelial cell line RWPE-1, and that of BPH-1 benign prostatic hyperplasia (BPH) epithelial cell line or OVCAR3 ovarian carcinoma cell line, with 1,25(OH) 2 D 3 , increases the intracellular levels of glucose-6-phosphate dehydrogenase (G6PDH), an enzyme which regulates the intracellular levels glutathione (Bao et al, 2008;Kovalenko et al, 2010;Zhang et al, 2005). This effect ultimately protects cells from apoptosis induced by H 2 O 2.…”
Section: Induction Of Antioxidant Enzymesmentioning
confidence: 99%